Application Of Business Intelligence in Decision Support in Providing Assistance to Business Actors in Deli Serdang Regency Using The Decision Tree Algoritm - Andysah Putera Utama Siahaan; Muhammad Irsyad; Alviona Marsya; M Dico Triyadi (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research shows that the application of BusinessIntelligence can Increase accuracy and efficiency in decision – making process regarding the distribution of aid to business actors in Deli Serdang Regency. With the business Intelligence tools used, we are able to identify business actors who need the most hel and have the potential to grow and develop to become business actors who are on the rise. The results of data that has been managed and processed can show that the results of data produced can reduce inappropriate decision making and increase satisfaction for beneficiaries. It Is hoped that the implementation of Business Intelligence tools can become a role model for other regions in an effort to increase the empowerment of Business Actors.